A Study on Measurements of Different Dimensions of Maxillary Sinus by Computed Tomography in Adult Nepalese Population - Khanal, Umesh Prasad; Adhikari, Anupama; Humagain, Mukunda Prasad (Nepalese Journal of Radiology, 2018)
Introduction: Measurement of different dimensions of maxillary sinus and anterior wall thickness of maxillary sinus by Computed Tomography in normal Nepalese population Methods: Dimensions of 90 patients were measured in CT PNS using Syngovia Software. AP diameter, width and anterior wall thickness were measured in axial images and height was measured in coronal images. Results: The mean volume of maxillary sinuses in study of male population on left and right side were 17.09 cm3±3.89, 17.19 cm3 ±4 respectively whereas in female were 15.64 cm3±3.5 and 15.21cm3±3.2 respectively as shown in Table 1. This shows the volume of male was significantly larger than female with P- Value = 0.012 (<0.05). Similarly, the thickness of Anterior Wall (AW) of maxillary sinus was also measured in this study and the mean value of left and right side in male were 0.16cm± 0.04 and 0.15cm± 0.03 respectively and in female were 0.12cm± 0.04 and 0.14cm± 0.02 respectively. Conclusion: This study showed that CT is a reliable method for the measurement of different dimensions of the maxillary sinus. The result showed greater mean value of volume in male than female with significant differences. So this study concluded that the measurement of volume of maxillary sinus can help in the identification of gender which can be very useful for forensic sciences.